Guidebook Development for Writing PDSI Report with Language Error Analysis at Vocational High School in Makassar - Munggaran, Mahesa Admi Putra; Amir, Johar; Nur, Basri; Subrianto, Andi Aryan (Jurnal Lingua Idea, 2024)
This study is needed to create a solution for the problem of the lack of students' writing skills, especially in writing PDSI reports. The objective of this study is to determine (1) the process of developing the guidebook, (2) the validity of the developed guidebook, (3) the practicality of the developed guide, and (4) the effectiveness of the developed guidebook. This type of research is development research. The model used is the developed Borg and Gall model, which consists of eight stages. Data used in this study is divided into three sources: needs analysis data, product development data, and field test data. The instruments used in this study are an interview guide and a questionnaire. The data collection methods used are observation, interview, and questionnaire. The data analyzing method used is descriptive quantitative. The results of the study indicate that (1) it has succeeded in explaining in detail the procedure of developing guide book for writing PDSI reports with language error analysis based at SMK-SMTI Makassar, (2) this developed product has been proven valid with 86,25% validity percentage by first expert validator and 87,5% validity percentage by second expert validator, (3) this developed product has been proven practical with 89% practical percentage, (4) this developed product has been proven effective to improve students abilities based from 58,4 pre-test score to 86,6 post-test score. From the result of these studies, it can be concluded that guidebook development for writing PDSI reports with language error analysis based at SMK-SMTI Makassar is valid, practical, and effective.